The Effect of Minimum Wage, Investment, GRDP, and Technology Index on Indonesian Labor Absorption - Ummah, Siti Safi'atul; Yasin, Ach. (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
Labor issues become an obstacle to the development process in a country. This problem arises due to a lack of employment opportunities, so that the existing workforce is not maximally absorbed. This problem is not spared from several development factors including the minimum wage, investment, GRDP and technology index. With the aim of knowing the influence of the minimum wage, investment, GRDP and technology index variables with the Indonesian labor absorption variable in 2015-2019. Using secondary data obtained from BPS Indonesia and using panel data regression analysis techniques with the Fixed Effect model as the selected model and using classical assumption tests and hypothesis testing. The results of the hypothesis test show that the influence of the minimum wage, investment, GRDP and technology index variables has an effect on the labor absorption variable simultaneously. The magnitude of the effect (R²) by all independent variables shows that the minimum wage, investment, GRDP and technology index have an effect of 99.82% on the depnden variable (labor absorption). Keywords: Minimum Wage, Investment, GRDP, Technology Index, Labor Absorption